Estimates of the eligible population for Australia’s targeted National Lung Cancer Screening Program, 2025–2030 - Stephen Wade; Preston Ngo; Yue He; Michael Caruana; Julia Steinberg; Qingwei Luo; Michael David; Annette McWilliams; Kwun M Fong; Karen Canfell; Marianne F Weber (Public Health Research & Practice)
Australia’s National Lung Cancer Screening Program will commence in July 2025, targeted at individuals aged 50–70 years with a 30 pack-year smoking history (equivalent to 20 cigarettes per day for 30 years), who either currently smoke or have quit within the past 10 years. We forecasted the number of screening-eligible individuals over the first 5 years of the program using data from the 2019 National Drug Strategy Household Survey and the 2022 Australian Bureau of Statistics population projections. Multiple imputation integrated with predictive modelling of future or unmeasured smoking characteristics was used to address missing data and, simultaneously, to project individuals’ smoking histories to 2030. In 2025, 930 500 (95% prediction interval 852 200–1 019 000) individuals were estimated to be eligible, with the number meeting the criteria declining slightly during the years 2025–2030 in all Australian jurisdictions. Overall, 26–30% of those eligible will have quit smoking, and 70–74% will currently smoke. These estimates can be used in resource planning and as an indicative denominator to track participation rates for the program over time.